City of 201 gods : ilé-ifè in time, space, and the imagination - Olupona, Jacob K. (Jacob Kẹhinde), 1951- (ACLS Humanities E-Book., 2011)
In a study that challenges familiar Western modes of thought, Jacob K. Olupona focuses on one of the most important religious centers in Africa and in the world: the Yoruba city of ilé-ifè in southwest Nigeria. The spread of Yoruba traditions in the African diaspora has come to define the cultural identity of millions of black and white people in Brazil, Cuba, Puerto Rico, Trinidad, and the United States. Seen through the eyes of a native, this first comprehensive study of the spiritual and cultural center of the Yoruba religion tells how the city went from great prominence to near obliteration.